Institutions, Behavior of Agents and Efficiency - Sukharev Oleg, S. (Журнал институциональных исследований, 2016)
We study the efficiency criterion, describing the behavior and choices of agents, the influence of moral norms on the model of behavior, as well as the criterion of efficiency as an institution to assess the behavior and development of the economic system. Curve proposed institutional compromise that allows to determine the possibility of changes in the welfare of interacting agents and their compliance with ethical standards when welfare increases due to violation or compliance with these standards. For the purposes of this demonstration of the influence of the model of chart-based dilemmas Holmes-Moriarty. Incentives in determining the agents behaviors play a key role in their formation due to the moral principles of behavior. However, in economics there are situations when moral principles are derived certain behaviors or interactions agents. Holmes and Moriarty there is an alternative interaction, which they can not take advantage of, and there is a full range of alternatives that actually programs the strategic outcomes of interactions that reflect the curves of "institutional compromise." Choosing an agent of moral standards as a potential model determines its behavior and, most importantly, interaction with other agents, adhering to certain moral principles. Assess the condition and the possibility of using a static criterion of Pareto efficiency for the analysis of situations where it is important to measure the economic efficiency. Showing institutional aspects that must be considered in the application or formulation of new performance criteria. It is proved that there is a connection microeconomic efficiency / inefficiency and parameters of behavior of agents that actualizes the need to impact on the behavior of agents incentives to solve the task of changing the structure.